Epidemiology and pathology of Trichomonas gallinae in the common pigeon (Columba livia) - Begum, N; Mamun, MAA; Rahman, SA; Bari, ASM (Journal of the Bangladesh Agricultural University, 2010)
Pigeons (n=300) were examined during July 2007 to June 2008 in different areas of Mymensingh district. Of the pigeons examined, 202 (67.3%) were infected by Trichomonas gallinae (Rivolta, 1878). Prevalence of Trichomonas gallinae was higher in female pigeon (70.9%) than male pigeon (63.8%). Adult pigeons aged >3 months were comparatively more affected (75%) than the squab aged <30 days (72.1%) and the younger aged between 30 days to 90 days (64.7%). T. gallinae infection was significantly (P<0.01) lower in summer (48.4%) than rainy (69.8%) and winter (69.3%) seasons. Pathological lesions were confined in the crop, proventriculus and liver. There was an accumulation of greenish fluid and/or cheesy material in the crop and proventriculus. At necropsy, yellowish to grayish necrotic lesions were evident in the crop and proventriculus. On the other hand, the liver became congested where congestion of sinusoids and focal accumulation of heterophils in the parenchyma were found. But, no microscopic lesions were seen in the crop and proventriculus although gross lesions were more prominent in these two organs. Keywords: Trichomonas gallinae; Pigeons; Epidemiology; Pathology DOI: 10.3329/jbau.v6i2.4826 J. Bangladesh Agril. Univ. 6(2): 301-306, 2008